Schubert’s mise-en-abîme - Zeiher, Cindy (Filozofski vestnik, 2025)
In honor of the thirtieth anniversary of Joan Copjec’s important and influential text, Read My Desire: Lacan Against the Historicists, this essay explores how the psychoana-lytic conceptualization of desire operates musically as much as linguistically. If the un-conscious is structured like a language, then music is structured like a desire for a lan-guage to be already spoken for. Franz Schubert’s evocative lieder literally speak about music’s capacity to capture and tarry with desire as a force always to be reckoned with.
Keywords: glasba; Lacan, Jacques; music; psihoanaliza; psychoanalysis